Japanese species of the sawfly genus Nesodiprion (Hymenoptera, Diprionidae) - Hara, Hideho; Smith, David R. (Zootaxa, 2015)
Nesodiprion flavipes sp. nov. associated with Tsuga diversifolia (Maxim.) Mast. and N. kojimai sp. nov. associated with Abies veitchii Lindl. are described from Honshu, Japan. Additional taxonomic and biological information is given for other Japanese congeners, N. japonicus (Marlatt, 1898), N. albiventris Togashi, 1998, N. shinoharai Togashi, 1998, N. nigerrimus Togashi, 1998, N. kagaensis Togashi, 1998, N. niger Togashi, 2001 and N. tsugae Togashi, 2001. The males of N. shinoharai, N. kagaensis and N. tsugae are described for the first time. The host plants of N. shinoharai are Pinus spp. Nesodiprion kagaensis is newly recorded from Hokkaido, Japan, and its host plants are Pinus spp. and Larix kaempferi (Lamb.) Carrière. Larvae of N. japonicus and N. kagaensis are briefly described. A division of Nesodiprion into the following five species groups is proposed: N. tsugae group, N. niger group, N. flavipes group, N. japonicus group and N. shinoharai group. Additions to the key to Nesodiprion species by Hara & Smith (2012) are given.